ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI TINGKAT PENGUNGKAPAN LAPORAN KEUANGAN PEMERINTAH DAERAH KABUPATEN/KOTA DI PROVINSI JAWA TENGAH TAHUN 2015-2017 - Era Fatwa Amaliah; Haryanto Haryanto (Diponegoro Journal of Accounting, 2019)
This study was aimed analyze the factors that influence the disclosure level of Local Government Financial Report (LGFR) in Central Java. Disclosure of LGFR are guided by the Government Regulation Number 71 of 2010 on Government Accounting Standards (GAS). The samples in this study are 35 local government in Central Java with a 3-year observation period (2015-2017). The samples was selected using purposive sampling technique and acquired 105 samples. The analytical method in this study is multiple regression analysis using IBM SPSS version 23 software.            The result of this study indicate that local dependency level, capital expenditures, and audit findings have a positive effect on the LGFR disclosure level. While, the own-source revenue and total population do not affect the LGFR disclosure level.